Development of Eggshell-Based Orange Peel Activated Carbon Film for Synergetic Adsorption of Cadmium (II) Ion - Vonnie Merillyn Joseph; Chua, Shek Li; Erna Husna Kana; Koh, Wee Yin; Wen, Felicia Xia Ling; Nur’ Aqilah Md Nasir; Rovina Kobun (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Heavy metal contamination has spread around the world, particularly in emerging countries. This study aimed to assess the effectiveness of starch/eggshell/orange peel-activated carbon-based composite films in removing cadmium (II) ions from water samples. X-ray diffraction and scanning electron microscopy were used to characterize the composite films. The effect of Cd2+ was studied using a UV-Vis spectrophotometer and atomic absorption spectroscopy. The morphology of the composite film reveals a highly porous and rough surface with more open channels and a non-uniform honeycomb, indicating that the film has a high potential to adsorb Cd2+. The diffraction peaks for this film were found to be at 13.74°, 17.45°, 18.4°, and 23.6°, indicating a typical crystalline A-type packing arrangement within the starch granules. The results indicate that crystalline structure was unaffected by the addition of eggshell powder and orange peel-activated carbon. In 0.5 mg L−1 and 1.0 mg L−1 Cd2+ ions, the composite film removed 100% and 99.7% of the Cd2+, respectively, while the maximum removal efficiency for methylene blue was 93.75%. Thus, the current study shows that starch/eggshell/orange peel activated carbon film has a high potential for commercial activated carbon as a low-cost adsorbent.